The Effectiveness of Group Guidance with Film Media to improve Students' Empathy and Social Interaction - Mufiqoh, Aliyah; Puji Sugiharto, Dwi Yuwono; Anni, Catharina Tri (Jurnal Bimbingan Konseling, 2018)
The purpose of this studywas to know the effectiveness of group guidance with film media to improve students' empathy and social interaction. Meanwhile, the research design used in this studywas experimental method with one group pretest-posttest design. Moreover, the subjects of the study were 10 students with the criteria of having empathy and social interaction that were classified as low or fair. In addition, the hypothesis testing used by the researchers in this studycame from Wilcoxon Signed Ranks Test. The results showed that there was a significant difference of students'empathy between pretest and posttest where empathy at posttest was higher than pretest which meant that the implementation of group guidance with film media could improve students' empathy (Z = -2.803; p < 0.01). Also, there found a significant difference of students' social interaction between pretest and posttest where posttest social interaction was higher than pretest which meant that the implementation of group guidance with film media can improve students' social interaction (Z = -2.807; p < 0.01). In conclusion, this study confirms that group guidance with film media is effective to improve students' empathy and social interaction.